(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the current status of nursing human resources at the National Hospital of Acupuncture in 2023. Subjects and methods: A cross-sectional descriptive study was conducted using secondary data combined with a census of all 206 nurses working in clinical departments, paraclinical departments, centers, and functional units of the National Hospital of Acupuncture in 2023. Data sources included reports on nursing workforce status, job assignment records, professional statistical reports, training and commendation reports, as well as hospital documents and current regulations related to human resource management. Results: In 2023, the National Hospital of Acupuncture had 206 nurses, of whom 68.0% were female. The age group of 30–39 years accounted for the highest proportion (49.5%). Nurses with college-level education accounted for 50.0%, bachelor’s degree holders for 34.0%, and postgraduate degree holders for 1.9%. The most common monthly income ranged from VND 5,000,000 to under VND 8,500,000. The ratio of health workers to hospital beds was 1.04, which was lower than the benchmark stated in Joint Circular No. 08/2007/TTLT-BYT-BNV. The ratio of nurses to hospital beds was equivalent to 0.34 nurses per bed, or one nurse for every 2.95 beds. Conclusion: Nursing human resources at the National Hospital of Acupuncture showed a relatively stable structure in terms of gender, age, and professional qualification. However, the overall ratio of health workers to hospital beds remained lower than the current benchmark, and the distribution of nurses across departments should be further reviewed to ensure more appropriate and effective workforce utilization